Surface roughness of ion-sputtered micromold - Ali, Mohammad Yeakub; Bryan, N. K. A.; Hung, W. N. P.; Alauddin, M.; Yuan, S. (2001)
This paper discusses the development of mathematical models for the calculation of surface roughness of focused ion beam (FIB) sputtered microfeatures. The effective beam shape was characterized first and then the beam function was developed. Material function was developed from the inherent material properties. These two functions were then combined mathematically to develop the surface roughness models. The models were verified by sputtering single crystal silicon using 50 keV Ga ion FIB. The models were applied to fabricate microcavities which were successfully used for the replication of three dimensional (3D) polymer microcomponents.